Significant Level of Financial Risk on Capital Structure - Jothi, K. (Indian Journal of Finance, 2010)
Finance is to play a vital role in all organizations and so, it leads the finance department to be a team player which is constructively involved in all operations of the sector. While analyzing the financial problems of an organization, the principal contents of the financial management can be said to be, i) How large should enterprises be and how fast should it grow? ii) In what form should it hold assets? And iii) What should be the composition of its liabilities? These three questions deal with the major financial problems of the firm. As such, the financial manager is concerned with the solution of three major problems relating to financial operations of the firm corresponding to investment, financing and dividend decisions. Of these three decisions, the most important decision to be made by the financial manager is decisions on financing. Broadly, finance personnel must decide when, where, and how to acquire funds to meet the investment needs of the firm. The central issue before the finance personnel is to determine the proportion of equity and debt with the effects of financial and operating risk factors. The combination of debt and equity is known as the capital structure of the firm. The finance personnel must strive to obtain the best financing combinations or the optimum capital structure for the firm.